Enhancing pedagogical competence of teachers through merdeka curriculum teaching module preparation in Candimulyo, Magelang - Febru Puji Astuti; Reza Edwin Sulistyaningtyas; Khusnul Laely; Indiati Indiati (Community Empowerment, 2024)
Implementing the Merdeka curriculum at all education levels requires teachers to adapt to all its components, including the application of teaching modules in planning. Teaching modules are crucial for a well-prepared learning process, aiming to optimize children's development. This service activity aims to enhance teachers' understanding of preparing teaching modules to improve their pedagogical competence. The participatory rural appraisal (PRA) method is used to address partner problems. The results indicate an increase in knowledge about teaching module preparation based on the evaluation outcomes.